Topaz concentrate desiliconization with ammonium bifluoride - Andreev V. A.; Buinovsky (Buynovskiy, Buinovskii) A. S. Alexander Sergeevich; Andreev A. A. Artyom Andreevich; Dyachenko A. N. Alexander Nikolaevich (Chemistry, 2007)
Заглавие с титульного листа